KEDUDUKAN HUKUM ISBAT NIKAH LUAR NEGERI - Ramdani Wahyu Seruri (Asy-Syari'ah, 2016)
This paper is motivated by the number of Indonesian Workers (TKI) who work abroad to get married in Sirri, some of them occurred in Malaysia. Based on this background, the authors interested in explaining the legal position validation of marriage in outside the country. That is the legal basis for the implementation of validation of marriage outside the country, referring to the legislation, ranging from generalist like regulations of Law Number 48 Of 2009 about The Judicial Authorities of clause 60B and Law about Religious Courts, as well as the rule of lex specialist like Circular Supreme Court Number 10 Of 2010, appendix B SK Supreme Court Nomor 084/KMA/ SK/V/2011 on Permit Session Establishment Marriage (isbat nikah/validation of marriage) in The embassies of the Republic of Indonesia. procedures of case examination about validation of marriage in outside the country followed the procedural law applicable in the Religious Court, whereas KUA which the authorities listed about validation of marriage in outside the country is PPN (The Registrar of Marriage) located in The embassies of the Republic of Indonesia in each country.